1990
DOI: 10.1105/tpc.2.9.877
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Analysis of Pollen Development in Wild-Type Arabidopsis and a Male-Sterile Mutant.

Abstract: Microsporogenesis has been examined in wild-type Arabidopsis thaliana and the nuclear male-sterile mutant BM3 by cytochemical staining. The mutant lacks adenine phosphoribosyltransferase, an enzyme of the purine salvage pathway that converts adenine to AMP. Pollen development in the mutant began to diverge from wild type just after meiosis, as the tetrads of microspores were released from their callose walls. The first indication of abnormal pollen development in the mutant was a darker staining of the microsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 24 publications
5
79
0
1
Order By: Relevance
“…Staining of mutant pollen with DAPI indicated that this pollen can mature to the tricellular stage. The lack of 18:3 and jasmonate appears to affect pollen development at a stage later than that of any of the previously described mutations that result in the production of aborted or dead pollen in Arabidopsis (Regan and Moffatt, 1990;Chaudhury, 1993). Our best estimates of the timing of jasmonate action suggest that jasmonic acid or Na18:3 must be applied 12 to 24 hr before flower opening to ensure seed set corresponding to the middle of stage 12, as defined by Smyth et al (1990).…”
Section: Dlscusslonmentioning
confidence: 99%
See 1 more Smart Citation
“…Staining of mutant pollen with DAPI indicated that this pollen can mature to the tricellular stage. The lack of 18:3 and jasmonate appears to affect pollen development at a stage later than that of any of the previously described mutations that result in the production of aborted or dead pollen in Arabidopsis (Regan and Moffatt, 1990;Chaudhury, 1993). Our best estimates of the timing of jasmonate action suggest that jasmonic acid or Na18:3 must be applied 12 to 24 hr before flower opening to ensure seed set corresponding to the middle of stage 12, as defined by Smyth et al (1990).…”
Section: Dlscusslonmentioning
confidence: 99%
“…Double staining with fluorescein diacetate and propidium iodide was performed using the method of Regan and Moffatt (1990) with some alterations. A stock solution of 2 mg/mLfluorescein diacetate was made in acetone and added dropwise to 17% sucrose (whr).…”
Section: Microscopymentioning
confidence: 99%
“…However, light microscopy showed that tapetal cells were relatively thin compared to those from the wild type at the same stage of development (Fig. 7A) and the number of viable pollen grains tested by fluorescein diacetate stain was smaller the T-DNA insertion line (data not shown; Regan and Moffatt, 1990). RT-PCR analysis revealed that MYB99 is expressed solely in inflorescences and that the T-DNA insertion (which is localized in the second exon of MYB99, or 505 bp from the start codon of the cDNA) leads to a complete loss of transcript accumulation (Fig.…”
Section: Identification Of Novel Regulators Of Microsporogenesismentioning
confidence: 99%
“…Such mutants have been obtained in many species of higher plants (Kaul, 1988 ;Goldberg et al, 1993). In the selfpollinating species Arabidopsis thaliana, many ms mutants have been generated by chemical and irradiation mutagenesis (Van der Veen & Wirtz, 1968 ;Regan & Moffatt, 1990 ;Chaudhury et al, 1992Chaudhury et al, , 1994Dawson et al, 1993 ;Preuss et al, 1993), by T-DNA insertional mutagenesis (Feldmann et al, 1994 ;Glover et al, 1996 ;Park et al, 1996) and transposon mutagenesis .…”
Section: mentioning
confidence: 99%
“…In Arabidopsis, as in most species of flowering plants, the anther wall is comprised of four cell layers : the epidermis, endothecium, middle layer and tapetum (Foster & Gifford, 1974 ;Regan & Moffatt, 1990 ;Bowman, 1994). Anther dehiscence is a multi-step process which includes the lytic opening of a longitudinal line of weakness in the epidermis, known as the stomium, and retraction of the anther wall to widen the stomium and permit pollen release (Goldberg et al, 1993).…”
Section: mentioning
confidence: 99%